Attitudes and coping practices of using mobile phones for teaching and learning in a Uganda secondary school. (2nd January 2018) - Busulwa, Henry Ssebuliba; Bbuye, Julian
Abstract: This study investigated the opportunities for learning afforded by access to mobile phones, and the associated challenges created by their use in a peri-urban private secondary school in Uganda. The study was motivated by availability of phones with facilities to connect to the Internet and to access free open education resources (OERs), which if used appropriately, could support changes in pedagogy required to promote learning in rural schools in Uganda. Information was collected using interviews, observations and focus group discussions with parents, students and their teachers between June 2014 and July 2015. Results show a slow positive change in attitude amongst teachers and parents that phones are useful in learning; an increased enthusiasm and eagerness among students, and more engaging and interactive lessons. Some teachers found challenges in accessing education resources due to poor Internet connectivity, while others required skills and knowledge about appropriate OERs that promote interactive learning. The study recommends re-skilling of teachers to use mobile phones to access the Internet, use of OERs and ICT interactive pedagogies especially in schools with limited access to computers and Internet connectivity.